Neuroform Atlas Stent System for the treatment of intracranial aneurysm: primary results of the Atlas Humanitarian Device Exemption cohort. (22nd January 2019) - Jankowitz, Brian T; Hanel, Ricardo; Jadhav, Ashutosh P; Loy, David N; Frei, Donald; Siddiqui, Adnan H; Puri, Ajit S; Khaldi, Ahmad; Turk, Aquilla S; Malek, Adel M; Sauvageau, Eric; Hetts, Steven W; et al.
Abstract : Background and objective: Stent-assisted coil embolization is a well-established treatment of intracranial wide-necked aneurysms. The Neuroform Atlas Stent System is a new generation microstent designed to enhance coil support, conformability, deliverability, and improve deployment accuracy. We present the 1-year efficacy and angiographic results of the Humanitarian Device Exemption (HDE) cohort from the Atlas Investigational Device Exemption (IDE) clinical trial. Method: The Atlas IDE trial is a prospective, multicenter, single-arm, open-label study of unruptured wide-necked intracranial aneurysms treated with the Neuroform Atlas stent and approved coils. The primary efficacy endpoint was the rate of 12-month complete aneurysm angiographic occlusion (Raymond class I) without target aneurysm retreatment or significant parent artery stenosis (>50%) at the target location. The primary safety endpoint was the rate of major ipsilateral stroke or neurological death within 12 months. Imaging core laboratory and Clinical EventsCommittee adjudicated the primary endpoints. Results: 30 patients were enrolled at eight US centers, with 27 patients completing the 12-month angiographic follow-up. The mean age was 59.4±11.8 years and 24/30 patients (80%) were women. The mean aneurysm size was 5.3±1.7 mm and the dome:neck ratio was 1.1±0.2. Procedural technical success of Neuroform Atlas Stent deployment was 100%. 27 patients completed 12-month angiographic follow-up and 30 patients completed their 6-month follow-up. When applying the last observation carried forward method, the primary efficacy endpoint was observed in 26/30 patients (86.7%, 95% CI 69.3% to 96.2%) compared with 25/27 patients (92.6%, 95% CI 75.7% to 99.1%) who completed the 12-month angiographic follow-up. The primary safety endpoint of stroke occurred in one patient (3.3%), who made a complete clinical recovery at discharge. There were no neurological deaths. Conclusion: The Neuroform Atlas stent in conjunction with coils demonstrated a high rate of complete aneurysm occlusion at 12-month angiographic follow-up, with an improved safety profile in the HDE cohort. Clinical trial.gov registration number: NCT0234058 ;Results